PEMBERDAYAAN REMAJA MELALUI PROGRAM GENRE-SMART (GENERATION OF REPAIR - SEHAT MANDIRI AKTIF RESPONSIF TANGGUH) - Susila, Wahyu Dini Candra; Orizani, Chindy Maria; Qomariah, Siti Nur; Suroso, Heri (Community Development in Health Journal, 2024)
Introduction & Aim: Qualified adolescents play an important role in achieving the continuity and success of national development goals, so they need serious attention to improve their quality, especially in terms of health. Adolescents are the population in the age range of 10-19 years with the number of adolescent groups in the world estimated at 1.2 billion or as much as 18% of the total population in the world. The complexity of health problems in adolescents requires comprehensive and integrated handling that involves all elements from across programs and across related sectors. Therefore, a program that involves adolescents directly is needed to identify the needs and expectations of adolescents towards the implementation of adolescent health programs. The purpose of this activity is to form adolescent cadres and provide training on adolescent posyandu through the Genre-Smart program. The Genre-Smart program is a forum for adolescents to apply the program that has been given to form adolescent health cadres. Method of Activity: The method of implementing this activity begins with youth regeneration. Teenagers are trained with Genre-Smart program materials. The program was followed by evaluation for 2 weeks and pre and post tests were conducted. Results: The results obtained data on the characteristics, knowledge, attitudes and skills of Genre-Smart youth cadres. Discussion: The Genre-Smart program using presentation, demonstration and simulation methods is considered effective for changing adolescent behavior, but organizations in the community need to be regulated in policies in the form of decrees so that they have legal force. Hope that the program that has been implemented will be supported by the coaches and stakeholders in the local area.